The Influence of Sedimentation to The Morfology Change of Serang River Estuary at The National Strategic Area Yogyakarta International Airport (Ksn Yia) - Dibo Separnu; M Syahril Badri Kusuma; Dantje K Natakusumah (Jurnal Teknik Sipil, 2023)
Abstrak.